Presidential Candidate and Term of Office and Vice President in Indonesia - Sholehudin, Miftahus; Sukadi, Imam (Pancasila International Journal of Applied Social Science, 2025)
Article 7 of the 1945 Constitution of the Republic of Indonesia still has weaknesses. Its formulation can still be interpreted differently from the original intent , which emphasized the term limits of the president and vice president. The formulation of Article 7 of the 1945 Constitution of the Republic of Indonesia reads "The President and Vice President hold a term of office for five years, and can be re-elected to the same office, only for one term". In the future, so that it is not interpreted differently, the formulation of Article 7 of the 1945 Constitution of the Republic of Indonesia should read "The President and Vice President hold a term of office for five years, and can be re-elected for only one term".